2019
DOI: 10.1007/s10815-019-01411-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethnical and sociocultural differences causing infertility are poorly understood—insights from the Arabian perspective

Abstract: Infertility is acknowledged worldwide as a major health concern. Although global levels of primary and secondary infertility have hardly changed between 1990 and 2010, significant regional differences have been reported. The prevalence of infertility in women has been estimated to be one in every seven couples in the western world and one in every four couples in developing countries. Male infertility may be under-reported in some regions due to an unwillingness of the male partner to undergo fertility investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…In another study of 62 infertile men with a family history of consanguinity, severe sperm defects including the tail defect ''stunted tail'' and the acrosome defect ''round head'' were detected in 27% of the cohort (10). A recent study suggested that severe forms of male factor infertility may be more frequent in Eastern and Muslim populations, in which the practice of consanguineous marriage is very high compared with Western countries (5). Ethnical and sociocultural differences across Middle Eastern countries may contribute to regional variations in the frequency and the severity of male factor infertility compared with other parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study of 62 infertile men with a family history of consanguinity, severe sperm defects including the tail defect ''stunted tail'' and the acrosome defect ''round head'' were detected in 27% of the cohort (10). A recent study suggested that severe forms of male factor infertility may be more frequent in Eastern and Muslim populations, in which the practice of consanguineous marriage is very high compared with Western countries (5). Ethnical and sociocultural differences across Middle Eastern countries may contribute to regional variations in the frequency and the severity of male factor infertility compared with other parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The term ''consanguinity'' refers to a relationship between two people who share a common ancestor or blood. The Middle East has high rates of consanguineous marriages, with overall rates reported at 20% to 50% and up to 80% in certain regions (5). Most consanguine marriages are between first cousins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…59 In addition to the prevailing evaluation criteria of infertile males, country-specific or region-specific counselling and treatment modalities should be established. 60…”
Section: Future Focusmentioning
confidence: 99%
“…VitD deficiency is the most common vitamin deficiency worldwide and can be found in all ethnicities and age groups. Despite the abundance of sunlight and the concealing dress code owing to sociocultural/religious habits, the highest prevalence of VitD deficiency in the world is found in the Middle Eastern Arab population (96.9%) (30)(31)(32). Moreover, this population is characterized by low anti-Müllerian hormone (AMH) levels (33,34).…”
Section: Introductionmentioning
confidence: 99%